Microbial diversity drives carbon use efficiency in a model soil - Luiz A. Domeignoz-Horta (Nature Portfolio, 2020)
Microbial carbon use efficiency has an important role in soil C cycling. Here the authors test the interactive effects of temperature and moisture and manipulate microbial community composition in soil microcosms, showing a positive relationship between microbial diversity and CUE that is contingent on abiotic conditions.